New foundations for the physical mechanism of variable chlorophyll a fluorescence. Quantum efficiency versus the light-adapted state of photosystem II - Garab, Győző; Magyar, Melinda; Sipka, Gábor; Lambrev, Petar H (Journal of experimental botany, 2023)
Photosystem II (PSII) uses solar energy to oxidize water and delivers electrons to fix CO2. Although the structure at atomic resolution and the basic photophysical and photochemical functions of PSII are well understood, many important questions remain. The activity of PSII in vitro and in vivo is routinely monitored by recording the induction kinetics of chlorophyll a fluorescence (ChlF). According to the 'mainstream' model, the rise from the minimum level (Fo) to the maximum (Fm) of ChlF of dark-adapted PSII reflects the closure of all functionally active reaction centers, and the Fv/Fm ratio is equated with the maximum photochemical quantum yield of PSII (where Fv=Fm-Fo). However, this model has never been free of controversies. Recent experimental data from a number of studies have confirmed that the first single-turnover saturating flash (STSF), which generates the closed state (PSIIC), produces F1<Fm, and have uncovered rate-limiting steps (Δτ1/2 half-waiting times) in the multi-STSF-induced F1-to-Fm increments that originate from the gradual formation of light-adapted charge-separated states (PSIIL) with significantly increased stability of charges compared to the PSIIC state that is elicited by a single STSF. All the data show that the interpretation of ChlF must be laid on new foundations. Here, we discuss the underlying physical mechanisms and the significance of structural/functional dynamics of PSII as reflected by ChlF and variations in the novel parameter Δτ1/2.
Keywords: purple bacterial reaction center; Chlorophyll a fluorescence induction; photochemical quantum efficiency; conformational changes; dielectric relaxation; F v/Fm; electric field effects; photosystem II; QA-model; light-adapted charge-separated state